2007
DOI: 10.3892/or.18.4.811
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate (vitamin C) induces cell death through the apoptosis-inducing factor in human breast cancer cells

Abstract: Abstract. Although ascorbate (Vitamin C) has been shown to inhibit cell growth and induce cell death in variety of cancer cells, results reported in other studies are inconsistent with this conclusion. It was previously reported that ascorbate induces apoptosis in human breast cancer cells. However, the molecular mechanism for this is not clear. In this study, we demonstrate that ascorbate induces cell death through the apoptosis-inducing factor (AIF) in the human breast cancer cell lines, SK-BR3 and Hs578T, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 21 publications
3
54
1
Order By: Relevance
“…However, it has been difficult to generalize a molecular mechanism in all types of susceptible cancer cells, because H 2 O 2 and ROS have promiscuous targets in the cell Levine et al 2011). Some studies indicated that ascorbate induced apoptosis in some types of cancer cells (Carosio et al 2007;Hong et al 2007;Lin et al 2006), while others showed that the ascorbateinduced cell death was caspase independent, and apoptosis was not the main type of cell death induced by ascorbate (Chen et al 2005;Kang et al 2003;Ohtani et al 2007;Verrax et al 2004;Verrax et al 2005). Autophagy was also suggested to be causing death when cells were treated with ascorbate (Cullen 2010;Du et al 2010).…”
Section: Mechanisms Of Actionsmentioning
confidence: 96%
“…However, it has been difficult to generalize a molecular mechanism in all types of susceptible cancer cells, because H 2 O 2 and ROS have promiscuous targets in the cell Levine et al 2011). Some studies indicated that ascorbate induced apoptosis in some types of cancer cells (Carosio et al 2007;Hong et al 2007;Lin et al 2006), while others showed that the ascorbateinduced cell death was caspase independent, and apoptosis was not the main type of cell death induced by ascorbate (Chen et al 2005;Kang et al 2003;Ohtani et al 2007;Verrax et al 2004;Verrax et al 2005). Autophagy was also suggested to be causing death when cells were treated with ascorbate (Cullen 2010;Du et al 2010).…”
Section: Mechanisms Of Actionsmentioning
confidence: 96%
“…In contrast, ascorbate-mediated cytotoxicity in breast cancer cell lines, SK-BR3 and Hs578T, involved nuclear translocation of the mitochondrial apoptosis-inducing factor (AIF) protein (36). Inhibition of mitochondrial AIF release only partially inhibited cell death.…”
Section: Cell Death Mechanisms: Autophagy Apoptosis and Necrosismentioning
confidence: 98%
“…In detail, pro-apoptotic effects of ascorbate were observed in epithelial tumor cells derived from different cancers such as hepatocellular carcinoma [11,37], esophageal cancer [38], breast cancer [39], non-small cell lung cancer [40] and gastric cancer [41]. Ascorbate seems to have a preferential toxicity toward melanoma cells [42].…”
Section: Antiproliferative Impact Of Ascorbate On Epithelial and Mesementioning
confidence: 99%